Scrawny pinky. - Ooi, Peck Toung; Choo, Raymond Pow Yoon; Ong, Bee Lee (Universiti Putra Malaysia Press, 2013)
This is a problem-based learning (PBL) to help students to identify the veterinary problems in a pig farm, to formulate hypothesis for the veterinary problems in the farm, and to investigate problems and defend a definite diagnosis.